Regulation of Renal Ion Channels by Serum and Glucocorticoid Inducible Kinase Isoforms, Ubiquitin Ligase Nedd4-2 and NHE3 Regulating Factor 2 in the Xenopus Laevis Oocyte Expression System - Embark, Hamdy; Justus Liebig University Giessen (My University, 2004)
Die Serum und Glucocorticoid-abhängige Protein-Kinase (SGK) ist eine Serin/Threonin-Proteinkinase, die über eine Signalkaskade via Phosphatidylinositide 3-Kinase (PI3-kinase) und 3-Phosphoinositid-abhängige Proteinkinase 1 (PDK1) phosphoryliert und damit aktiviert wird. Auf gleichem Wege werden die später entdeckten Isoformen der SGK, die SGK2 und SGK3 aktiviert. Über den genannten Signalweg stimuliert insulin-like growth factor 1 (IGF-1) die drei Kinasen. Darüberhinaus werden sie durch oxidativen Stress aktiviert. Die Transkription der SGK1, nicht aber der SGK2 und SGK3, wird durch Serum, Glucocorticoide, Aldosteron, hohe extrazelluläre Osmolarität und transforming growth factor beta (TGF-& #61538;) gesteigert. Die mutmaßliche Rolle der SGK1 und seiner Isoformen SGK2 und SGK3 in der Regulation renaler Ionenkanäle, die für Kalium-, Kalzium- und Chloridtransport verantwortlich sind, ist untersucht worden. In der Niere ist das SGK1 Expressionsniveau in Epithelzellen des distalen Tubulus und des Sammelrohrs sehr hoch. Bei hohen Glukosekonzentrationen werden SGK1 Transkripte auch im aufsteigenden Ast der Henle-Schleife nachgewiesen. NHERF2 und SGK1 interagieren miteinander und steigern damit die ROMK1 Aktivität, indem sie vor allem die Anzahl der Ionenkanäle in der Zellmembran erhöhen. Dabei interagiert SGK1 mit NHERF2 über dessen zweite PDZ Domäne. Eine Deletion der zweiten PDZ Domäne oder der vermeintlichen PDZ Bindungsstelle im ROMK1 Protein verhindert die Kanalstimulation. Diese Interaktion erlaubt die Integration genomischer Regulation und Aktivierung durch SGK1 und NHERF bei der Kontrolle der ROMK1 Aktivität und der renalen Kaliumausscheidung. Ferner wurde die Wirkung von Serum und Glucocorticoid induzierten Kinase (SGK) Isoformen und NHE3 Regulating Factor 2 (NHERF2) auf den epithelialen Kalcium Kanal (ECaC1) untersucht. Während SGK1 und SGK3 und NHERF2 eine ECaC1 Stimulierung, die durch den Ca2+-abhängingen Chloridstrom sowie die radioaktiv markiertes Ca2+ Aufnahme bestimmt wird, zeigen, haben SGK2 und Protein kinase B (PKB) unabhängig von NHERF2 keinen solchen Effekt. Die konstitutiv aktive Form S422DSGK1 und die inaktive K127NSGK1 wurden hergestellt. S422DSGK1 aber nicht K127NSGK1 zusammen mit NHERF2 verfügt immer noch über die Stimulationswirkung auf ECaC1. Der Kinase-hemmer Chelerythrin (10 µM) inhibiert die Aktivität von ECaC1. Pull-down Assays zeigen die Interaktion vom Carboxy-Ende des ECaC1 mit NHERF2, während funktionelle Experimente die Herabsetzung der Stimulationswirkung von SGK1 und einer NHERF2 mit deletierter zweiter PDZ Domäne zeigen. Die Schlussfolgerung ist, dass SGK1 ECaC1 durch Interaktion mit dem zweiten PDZ Domain von NHERF2 stimuliert. NHERF2 bindet an das Carboxy-Ende Tail von ECaC1, welches ECaC1 dadurch mit dem Aktin Zytoskellet stabilisiert. Letztendlich wurde zudem der Effekt der SGK Isoformen und der Ubiquitin Ligase Nedd4-2 auf den renalen, epithelialen Chloridkanal (ClC-Ka/barttin) untersucht. Expression von ClC-Ka/barttin verursacht einen schwach einwärts gleichrichtenden Strom, der signifikant durch die Koexpression von Nedd4-2 herabgesetzt wird. Die Koexpression von S422DSGK1, SGK1 oder SGK3, aber nicht die Koexpression von SGK2 oder K127NSGK1, stimulierte den Strom signifikant beziehungsweise hob teilweise den Effekt von Nedd4-2 auf. Die Herrunterregulation von ClC-Ka/Y98Abarttin wird durch die Elimination des PY Motifs im ClC-Ka/Y98Abarttin aufgehoben. Die vorliegenden Beobachtungen legen einen neuen Regulationsmechanismus für ClC-Ka offen, der höchstwahrscheinlich in der Transportregulation in der Niere und im Innenohr beteiligt ist.

The Serum and Glucocorticoid induced protein Kinase (SGK) is a member of the serine/threonine protein kinase gene family and is activated by phosphorylation in response to signals that stimulate phosphatidylinositide 3-kinase (PI3-kinase). This process is mediated by 3-phosphoinositide-dependent protein kinase 1 (PDK1). Two additional isoforms of SGK have been identified, termed SGK2 and SGK3. SGK (1-3) are all strongly activated by phosphorylation in response to oxidative stress (e.g. H2O2) and insulin-like growth factor 1 (IGF-1). SGK1 RNA is induced in response to serum and/or glucocorticoids, aldosterone, high extracellular osmolarity and transforming growth factor beta (TGF-). The putative role of SGK1 and its isoforms in the regulation of renal ion channels implicated for potassium, calcium and chloride transport has been examined. In kidney, SGK1 transcript levels were excessively high in the distal tubule and collecting duct epithelial cells. SGK1 transcripts were also detected in thick ascending limb epithelial cells, when glucose concentrations are high. NHERF2 and SGK1 interact to enhance ROMK1 activity in large part by enhancing the abundance of channel protein within the cell membrane. SGK1 interacts with NHERF2 through the second PDZ domain of NHERF2. Deletion of the second PDZ domain or of the putative PDZ binding motif on ROMK1 abolishes channel stimulation. This interaction allows the integration of genomic regulation and activation of SGK1 and NHERF2 in the control of ROMK1 activity and renal K+ excretion. Phosphorylation by SGK1 or introduction of negative charge at serine44 shifts the pH sensitivity of the channel and contributes to the stimulation of maximal channel activity by the kinase. Furthermore, the effect of serum and glucocorticoid induced kinase (SGK) isoforms and NHE3 regulating factor 2 (NHERF2) on epithelial calcium channel ECaC1 (TRPV5) has also been examined. Since coexpression of SGK1 or SGK3 and NHERF2 leads to stimulation of ECaC1 determined by measurement of Ca2+ dependent chloride current as well as radioactively labelled Ca2+ uptake, SGK2 and protein kinase B (PKB) failed to enhance ECaC1 irrespective of NHERF2. Since the stimulating effect of SGK1 and NHERF2 on ECaC1 is abolished by ruthenium red and absent in the presence of ionomycin, it can be concluded that ECaC1 is stimulated in a direct way. Interaction of SGK1 and NHERF2 is then extensively studied by generating constitutively active S422DSGK1, and the inactive form K127NSGK1. S422DSGK1 but not K127NSGK1 can mimic the stimulating effect of wild type SGK1 coinjected with NHERF2. The kinase inhibitor chelerythrine (10 µM) inhibits ECaC1 activity. Moreover, pull-down assay shows the interaction of the carboxy-tail of ECaC1 and NHERF2 whereas functional experiments show the abolishment of the stimulatory effect of SGK1 and NHERF2 who s second PSD 95/Drosophila disk large/ZO-1 (PDZ) domain has been deleted. It is thus concluded, that SGK1 stimulates ECaC1 by interaction with the second PDZ domain of NHERF2. NHERF2 then binds to the carboxy-tail of ECaC1 rendering a stabilization of ECaC1 by mediating interaction with actin cytoskeleton via ezrin. Finally, the effect of serum and glucocorticoid induced kinase (SGK) isoforms and ubiquitin ligase Nedd4-2 on renal epithelial Cl- channel (CIC-Ka/barttin) has also been studied. Expression of ClC-Ka/barttin induces a slightly inwardly rectifying current which is significantly decreased upon coexpression of Nedd4-2. The coexpression of S422DSGK1, SGK1 or SGK3, but not of SGK2 or K127NSGK1 significantly stimulated the current and reversed the effect of Nedd4-2. The down-regulation of ClC-Ka/barttin is abolished by elimination of the PY motif in ClC-Ka/Y98Abarttin. The present observations disclose a novel mechanism regulating ClC-Ka which presumably participates in the regulation of transport in kidney and inner ear.
Regulation renaler Ionenkanäle durch SGK, Nedd4-2 und NHERF2 durch Expression Xenopus Laevis Oocyzen System
Keywords: ddc:630